First records of echinoderms (Echinodermata) in shallow waters of Corn Island, Caribe, Nicaragua - Quinn-Lampson, Shaungnessy Roshelle; Benito-Sandino, Osmar; Solís-Marín, Francisco Alonso; Arriaga-Ochoa, Julio; Laguarda-Figueras, Alfredo (Revista de Biología Tropical, 2015)
There are few works on ecology and diversity of echinoderms in Nicaragua. Studies of many faunal groups of marine invertebrates, in particular which should focus on the fauna of tropical areas, have been scarce or have received only limited attention from the scientific community and government authorities of the South Atlantic Autonomous Region (RAAS) of Nicaragua. Scientific research on these groups has targeted mainly resources of commercial importance (e.g. spiny lobster, Panulirus argus). There is lack of information regarding the faunal biodiversity of Corn Island in general. The echinoderm fauna studied in this work comes from a wide variety of environments, from the rocky coastal area, sandy beaches, sea grass to areas of coral reef. Echinoderms were collected, from 14 points in a variety of marine substrates, aided by SCUBA diving equipment during the period from August 2012 to March 2013. There was a total of 41 species corresponding to four classes: three species of Asteroids, 16 species of ophiuroids, 11 species of Echinoids and 11 species of holoturoids. The most common species was Ophiolepis impressa present in ten of the 14 localities, followed of Diadema antillarum, Eucidaris tribuloides and Ophioderma cinerea who were present at seven locations each, respectively. The less common species were Clypeaster rosaceus, Leodia sexiesperforata, Meoma ventricosa and Ophioderma guttata. The study of echinoderms in diverse marine habitats facilitates the comparison of the state of fluctuation of those communities along time. Whether they were natural or caused by human activities. Therefore, the present study expands knowledge about the species of echinoderms that live in shallow areas of Corn Island (between 0-10 m depth), so able to establish measures for the conservation of these species.